Mapping Building Outdoor to Analysis Noise Leq with Matlab and 3DField - Risky Via Feriyanti (Universitas Bina Sarana Informatika, 2026)
Noise Level Standards are the maximum limit of noise levels that are permitted to be released into the environment from businesses or activities so that they do not cause harm to human health and environmental comfort. Sound Level Meter is a tool used to measure noise, unwanted sounds, or those that can cause pain in the ears. Sound Level Meters are usually used in work environments such as the aviation industry, malls, campuses and so on. This time the Sound Level Meter was used to measure noise in the Animal Health Building environment at Gadjah Mada University which was carried out on Friday 17 February 2017 from 13.00 WIB to 17.00 WIB. Sound Level Meter is used to measure noise between 30-130 dB in dB units from frequencies between 20-20,000Hz. Research was also carried out during the Practicum Class for the Analysis and Instrumentation Course. The research is carried out by holding the Sound Level Meter parallel to the practitioner's head and the results will be obtained after the Sound Level Meter sounds by waiting for an interval of 5 seconds when the dB value in the Sound Level Meter is stable, then the resulting dB value is written on a sheet of paper that has been made in a table. The aim of the practicum is so that students can understand the sound phenomena that occur in our environment, understand the level of noise that occurs in our environment and understand how the Sound Level Meter works clearly.